Factors Affecting Revenue Sea Fresh Fish Traders Retailersin the Pasar Bawah Pekanbaru - Ivada, Christy Leona; Yulinda, Eni; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 23th – 30th May 2013. This study aimed to know of fresh sea fish retailers income. Influence of these factors (the amount of capital held, the amount of fish sold, the price of fresh fish and trying experience) to income retailers in the Pasar Bawah Pekanbaru. Knowing the number of consumers who visit the fish market was moved to after the Sago Street. The method used in this study is a survey method with 20 respondents..The results of this study show the number of 20 respondents, 13 respondents or 65% soul traders have up to Rp.7.500.000 Rp.1.900.000 income permonth. With increasing capital, long sought, the amount off is hand fish prices will increase revenues fresh fish retailers. With the move from the Fish Market Down Market Street to the Sago be coming traders make income increases because consumers who visit be come more crowded.Keyword : Income, Pasar Bawah, Retailers